2015
DOI: 10.1007/s40263-015-0291-6
|View full text |Cite
|
Sign up to set email alerts
|

Does Guanfacine Extended Release Impact Functional Impairment in Children with Attention-Deficit/Hyperactivity Disorder? Results from a Randomized Controlled Trial

Abstract: BackgroundIn clinical trials of medications to treat attention-deficit/hyperactivity disorder (ADHD) in children, effects on functional impairment have been less well-studied than changes in ADHD symptoms.ObjectiveData regarding functional impairment were analyzed from a multicenter, double-blind, placebo-controlled study of guanfacine extended release (GXR) in children with ADHD, using the Weiss Functional Impairment Rating Scale–Parent Report (WFIRS-P). The correspondence of changes in WFIRS-P scores with sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…1 ). In support of this conceptualization, severity of or improvement in ADHD symptoms correlated moderately to strongly (but not perfectly) with severity of or improvement in functional impairment and HRQoL deficits, both in the included studies for which this was reported [ 42 , 62 , 66 , 86 ] and elsewhere in the literature [ 18 , 19 , 21 , 32 , 47 , 81 , 92 , 95 ]. Furthermore, effect sizes (when available) of active medications versus placebo were smaller for functional or HRQoL outcomes than for symptom-based outcomes in nearly all of the included studies (Tables 4 , 5 ).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…1 ). In support of this conceptualization, severity of or improvement in ADHD symptoms correlated moderately to strongly (but not perfectly) with severity of or improvement in functional impairment and HRQoL deficits, both in the included studies for which this was reported [ 42 , 62 , 66 , 86 ] and elsewhere in the literature [ 18 , 19 , 21 , 32 , 47 , 81 , 92 , 95 ]. Furthermore, effect sizes (when available) of active medications versus placebo were smaller for functional or HRQoL outcomes than for symptom-based outcomes in nearly all of the included studies (Tables 4 , 5 ).…”
Section: Discussionmentioning
confidence: 66%
“…Five of the nine studies that assessed functional impairment in children and adolescents used the parent-rated WFIRS-P. Four of these five studies (three short-term studies and one randomized withdrawal study) reported significant placebo-adjusted effects of treatment on WFIRS-P total score (Table 4 ) [ 14 , 15 , 51 , 86 ]. Scores in the Family domain and the Learning and School domain were most consistently improved relative to placebo in these studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The objective of this study is to determine the extent to which children and adolescents who meet the conventional definitions for symptom improvement and remission also meet empirical criteria for functional improvement and remission. Previous clinical trials have demonstrated that the WFIRS-P is sensitive to change in functional impairment (Banaschewski et al 2013 , 2014 ; Stein et al 2015 ; Wilens et al 2015 ; Nagy et al 2016 ) and sensitive to change as measured against change in ADHD symptoms (Gajria et al 2015 ).…”
Section: Methodsmentioning
confidence: 99%